Reproduction of Multiculturalism in the Development of Information and Communication Technology at Islamic Higher Education Institutions in Indonesia - Abidin Wakano, Saidin Ernas, Ummu Sai’dah (International Journal of Advanced Science and Technology, 2020)
In the last decade, the concept of multiculturalism has become one of the ideas of diversity management that has emerged in Islamic campuses in Indonesia, especially those under the Ministry of Religious Affairs. This paper aims to describe how the dynamics of Islamic higher education institutions understand and apply the idea of multiculturalism in the development of Information and Communication Technology. Based on the qualitative studies carried out in three State Islamic Religious Higher Education Institutions in Indonesia, namely IAIN Ambon, UIN Sahid Jakarta and UIN Ar-Raniri Banda Aceh, two important things were found. First, although the idea of ​​multiculturalism emerged from the historical experience of the Western world, it has been adapted as part of academic discourse on Islamic campuses because it is considered relevant to Islamic teachings on diversity. Second, the institutionalization of the idea of ​​multiculturalism in academic systems and life can be seen in three models. The ordinary acceptance model because multiculturalism is not considered an important idea needed by the academic community on a campus, as in the case of UIN Ar-Raniri Banda Aceh. Meanwhile the symbolic acceptance model in which multiculturalism is adapted has been applied at IAIN Ambon, which has openly adapted multiculturalism in the vision and mission of the institution. The substantive model adopted by the academic community at UIN Syarif Hidayatullah Jakarta has the opportunity to internalize the idea of ​​multiculturalism more strongly and deeply.